PEMBERIAN TEPID SPONGE TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DI RUANGAN SP2KP ANAK RSUD PROF. DR. H. ALOEI SABOE KOTA GORONTALO - Andi Akifa Sudirman; Dewi Modjo (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Handling of fever can be done bypharmacological action that is giving antipyretic drugs and non-farmakologis action is additional action in reducing the heat after the administration of antipyretic drugs such as warm compresses (tepid sponge). Tepid sponge is a procedure 10 increase the control of body heat loss through evaporation and conduction that is usually done in patients with high fever. The purpose of this study was to determine the effect of tepid sponge in the decrease in body temperature in children at RSUD Prof. Dr. H. Aloei Saboe Gorontalo City. This study used quation experiment with pretest and postest study design with two treatments. In this study using two groups that are selected as the first group of research objects to get treatment while the second group did not get treatment. The sample in this study was a total of 21 people for the control group and 21 people for the intervention group. The results showed that there was an effect of tepid sponge on the decrease of body temperature in children in SP2KP children room at RSUD Prof. Dr. H. Aloei Saboe with P value = 0,000 (P 0,005).